2018
DOI: 10.1386/tear.16.1.75_1
|View full text |Cite
|
Sign up to set email alerts
|

Virtual reality and human consciousness: The use of immersive environments in delirium therapy

Abstract: Immersive virtual environments can produce a state of behaviour referred to as ‘presence’, during which the individual responds to the virtual environment as if it were real. Presence can be arranged to scientifically evaluate and affect our consciousness within a controlled virtual environment. This phenomenon makes the use of virtual environments amenable to existing and in-development forms of therapy for various conditions. Delirium in the intensive care unit (ICU) is one such condition for which virtual r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…All included studies were published between 2017 to 2020 18,43‐66 with the majority published in 2020 18,48,51‐53,56‐58,61,64,65 . The country of study varied with studies taking place in France, 55,56 Netherlands, 58,59,63 Singapore, 60 South Korea, 51,52 Switzerland, 45‐47,57 United Kingdom, 53,54 and the United States 18,43,44,48‐50,61,64,65,67 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All included studies were published between 2017 to 2020 18,43‐66 with the majority published in 2020 18,48,51‐53,56‐58,61,64,65 . The country of study varied with studies taking place in France, 55,56 Netherlands, 58,59,63 Singapore, 60 South Korea, 51,52 Switzerland, 45‐47,57 United Kingdom, 53,54 and the United States 18,43,44,48‐50,61,64,65,67 .…”
Section: Resultsmentioning
confidence: 99%
“…The remaining papers were excluded due to not using VR headsets or being a commentary piece (see Figure 1 for PRISMA flow diagram 42 ). This resulted in 15 completed published studies and six registered trials being identified 18,43‐66 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…63 IVEs are now being investigated as part of a multimodal approach in screening for and preventing cognitive impairments as well as treating delirium in critical care settings. [65][66][67][68] Ideally, as these studies evolve, anesthesiologists will be able to use IVE software in their clinics to stratify delirium risk preoperatively, educate patients and their families about risks, and then implement a protocol (potentially with IVEs as a structural element) postoperatively to prevent or treat delirium. Imagine virtually transporting a delirious patient back into their home, where they can interact with their native environment and virtually present family?…”
Section: Anesthesia and Analgesiamentioning
confidence: 99%
“…The constructs of immersion, involvement, and emotion are difficult to disentangle from presence itself (Slater, 2003). Several studies have considered the difference between these terms and related constructs (Nacke and Lindley, 2008;Cummings and Bailenson, 2016;Suvajdzc et al, 2018). Generally, immersion refers to the outcome of immersive technology when evaluated objectively (Nilsson et al, 2016).…”
Section: Terminological Clarificationsmentioning
confidence: 99%